2003
DOI: 10.17221/4138-pse
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry analysis and seed germination of Amaranthus cruentus, A. retroflexus and their hybrid (A. × turicensis)

Abstract: A morphometric study of Amaranthus cruentus, A. retroflexus and their hybrid, A. × turicensis based on 75 plant samples (750 inflorescences), collected throughout the Olomouc-Holice area (Czech   Republic), is presented. Using multivariete methods (including cluster analysis and canonical discriminant analysis), the existence of three groupings of plants was proven. The hybrid exhibited intermediate values of the width and length of female tepals, length of awl-shaped bracts, and seed size w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Most Amaranthus hybrids exhibit relatively high levels of sterility (Gupta and Gudu, 1991). However, it is possible that the parental species could hybridize relatively easily (Lanta et al ., 2003). Hence, it is expected that these markers could be present due to natural or artificial inter-specific hybridization occurring in Amaranthus taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Most Amaranthus hybrids exhibit relatively high levels of sterility (Gupta and Gudu, 1991). However, it is possible that the parental species could hybridize relatively easily (Lanta et al ., 2003). Hence, it is expected that these markers could be present due to natural or artificial inter-specific hybridization occurring in Amaranthus taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the allogamy degree, this can vary from 5% up to 30% in individual plants (Hauptli, 1986). It has been reported that A. cruentus should hybridize relatively easily (Lanta et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Temple [22] reported the increase in the harvest of bean by seaweed extract by foliar application with high yield was increased by 25% observed respectively.The growth and development was determined by Principal Component Analysis (PCA) of morphometric characters that have relevance to other characters. Based on the analysis of PCA program, obtained a major component that is able to retain most of the information which was measured using the total diversity by using a bit of the main components only [23]. Effect of H.pinifolia at higher concentration of 800mg/g per pot treated showed maximum morphometric measurement observed and tabulated (Table 4).…”
Section: Resultsmentioning
confidence: 99%